Assessing Groundwater Contamination Risks from Dumpsite Leachate in Southwestern Nigeria: An Integrated Geophysical and Hydrochemical Review - Ogunkoya, Charles; Alasi, Taiwo Kamorudeen (UNIB Press, 2026)
Groundwater contamination from dumpsite leachate poses a significant environmental and public health challenge, particularly in developing regions like Southwestern Nigeria, where rapid urbanization and inadequate waste management exacerbate the problem. Leachate, a toxic byproduct of decomposing waste, infiltrates aquifers, posing a threat to water quality. This review synthesizes existing research on groundwater contamination risks from dumpsite leachate, employing geophysical and hydrochemical methods. The study aims to elucidate contamination mechanisms, evaluate methodological synergies, and identify gaps for future research. These methods collectively map leachate plumes and quantify pollutant concentrations, providing a comprehensive assessment of the extent of contamination. Geophysical surveys consistently identify low-resistivity zones (<100 Ωm) that correlate with dumpsite locations and hydrochemical indicators associated with leachate contamination. Hydrochemical data reveal elevated levels of heavy metals: chloride, nitrate, often exceeding both local and international limits. The Basement Complex geology, with fractured aquifers, exacerbates contaminant spread, while seasonal rainfall intensifies leachate mobility. The findings underscore thr critical need for improved waste management and groundwater protection in Nigeria. Persistent heavy metal contamination highlights long-term health risks, even where general water quality parameters appear acceptable. Alternative water sources should mitigate health impacts, while advanced remediation technologies and policy enforcement are essential for sustainable solutions.